The Influence of Emotional Intelligence, Job Satisfaction and Organizational Commitment on Organizational Citizenship Behavior and Employee Performance - Sindy Cahya Febrina; Rossi Isvandiari Dwi Putri (Fakultas Ekonomi Universitas Kadiri, 2023)
This study aims to determine the effect of emotional intelligence, job satisfaction and organizational commitment on organizational citizenship behavior and employee performance. The number of samples used were Bank Syariah Indonesia employees in the Malang area, for the sampling technique using saturated sampling. Collecting data by distributing questionnaires, using the Structural Equation Modeling (SEM) data analysis method. The results showed: 1) Emotional intelligence has no significant effect on OCB; 2) Job satisfaction has a significant effect on OCB; 3) Organizational Commitment has no significant effect on OCB; 4) Emotional intelligence has no significant effect on employee performance; 5) Job satisfaction has a significant effect on employee performance; 6) Organizational Commitment has no significant effect on employee performance; 7) OCB has a significant effect on employee performance; 8) Emotional intelligence, job satisfaction and commitment have a significant effect on employee performance through OCB.